STRENGTHENING FIRM PERFORMANCE THROUGH ENTERPRISE RISK MANAGEMENT AND SUSTAINABILITY PERFORMANCE: EVIDENCE FROM INDONESIA - Mariska Ramadana; Sellina Monica; Robby Krisyadi (Faculty of Economics and Business University of Mataram, 2026)
Growing global economic uncertainty and increasing sustainability demands in developing countries, including Indonesia, require firms to integrate risk management with sustainability strategies better. This study aims to examine the effect of ERM on firm performance while accounting for sustainability performance. The study employs panel data regression on 120 non-financial companies listed on the Indonesia Stock Exchange during the period 2019–2023. The results show that both ERM and sustainability performance have a positive effect on firm performance. However, sustainability performance does not mediate the relationship between ERM and firm performance. These findings suggest that risk management and sustainability contribute to firm performance through different pathways. In practice, firms need to align risk management with sustainability strategies better, while regulators should strengthen sustainability disclosure standards.